Asuhan Komplementer Tatalaksana Afterpain pada Ibu Postpartum : Literature Review - Nicky Danur Jayanti; Senditya Indah Mayasari (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
The puerperium is a period of recovery of the mother after giving birth which is characterized by the return of the reproductive organs to their pre-pregnancy state with a puerperal period of 6-8 weeks. During the recovery period, postpartum mothers will experience many changes, both physically and psychologically, if there is no assistance from both the family and health workers, it is possible that problems will occur beyond the postpartum period. Afterpain or often called abdominal cramps is pain caused by continuous contraction and relaxation of the uterus, usually lasting 3-4 days after delivery and is common in multiparas. Objective: to determine the complementary care afterpain management in postpartum mothers. The method used in this study uses a literature study or literature review. The selected articles were 4 reviews that matched the criteria with the topic of afterpain management in postpartum mothers without giving pharmacology and medical measures. Discussion: afterpain management for postpartum mothers can be given complementary care by giving effluarge massage therapy, sacral plexus massage, candle therapy, postpartum gymnastics, other care such as emptying the bladder, providing a comfortable position (prone position by propping the stomach with a pillow), providing relaxation techniques, early mobilization, adequate rest and fulfillment of balanced nutrition. The results of this literature study can be a management intervention in the management of afterpain complaints in postpartum mothers.